2020
DOI: 10.1186/s12960-020-00499-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and preparedness toward IPV care provision among nurses and midwives in Tanzania

Abstract: Background: With increasing recognition of intimate partner violence (IPV) as a public health challenge, nurses and midwives are recognized for their crucial role in providing front-line healthcare services for IPV. This study aimed to evaluate knowledge, attitude, and preparedness related to IPV care provision in health facilities among nurses and midwives in Tanzania. Methods: A self-administered anonymous questionnaire survey was conducted among nurses and midwives working in health facilities in the Mbeya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 21 publications
7
26
0
4
Order By: Relevance
“…This instrument has been adapted and widely used in multiple populations, cultures and languages [16,[21][22][23][24][25][26][27][28][29][30][31][32][33]. It was also used to measure the effectiveness of IPV training programs proposed to physicians [20], practicing general practitioners and residents of general practice [34], nurses [35], and healthcare providers working in fracture clinics [36].…”
Section: Introductionmentioning
confidence: 99%
“…This instrument has been adapted and widely used in multiple populations, cultures and languages [16,[21][22][23][24][25][26][27][28][29][30][31][32][33]. It was also used to measure the effectiveness of IPV training programs proposed to physicians [20], practicing general practitioners and residents of general practice [34], nurses [35], and healthcare providers working in fracture clinics [36].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that (58%) of the participants had not trained enough to manage IPV, as only (20%) of them reported reading their institution’s protocol within their hospitals, and (26%) had gained knowledge as part of the undergraduate medical/nursing curriculum. The current level of previous training was low compared to other studies in which the sample were healthcare providers [ 19 , 22 , 23 ], and higher than a sample of healthcare students [ 24 , 25 ]. These results draw attention to the need for educational training resources, health policies, and public advocacies that support the health care providers in building their competency in dealing with IPV cases in ER.…”
Section: Discussionmentioning
confidence: 61%
“…A systematic review found that nurses were not prepared to deal with IPV cases because they lacked the proper education and skills in identifying the symptoms and communicating with the victims [ 18 ]. Previous studies show that gender, educational level, work experience, and receiving preservice IPV training were associated with high scores in the knowledge of IPV [ 19 , 20 ]. With the uprising prevalence of IPV as a public health concern, nurses and physicians are recognized for their vital role in providing healthcare services for IPV.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as the results showed, nurses have not received specific and sufficient IPV training in their university studies. They also do not receive further training at their workplace (Alhalal, 2020; Ambikile et al, 2020; Gómez‐Fernández et al, 2017; Sundborg et al, 2012; Visentin et al, 2015; Zaher et al, 2014). Although IPV is included in the university nursing degree curriculum in Spain since 2008 (Order CIN/2134/2008, by which the requirements for the verification of official university degrees that enable the exercise of the profession of Nursing were obtained, 2008), a study published in 2019 found that 20% of the nursing training programmes in the country had not included this subject (Maquibar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They also do not receive further training at their workplace (Alhalal, 2020;Ambikile et al, 2020;Gómez-Fernández et al, 2017;Sundborg et al, 2012;Visentin et al, 2015;Zaher et al, 2014) (Maquibar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%